PEMBELAJARAN DI SEKOLAH DASAR DAN PERMASALAHANNYA - Afriana Tasya, Della; Ramadani, Sagita; Wahyuni; Ananda, Rizki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article discusses the challenges faced in implementing 21st-century learning in elementary schools, especially related to teachers' abilities to implement this approach. The aim of this research is to explore the role of teachers in 21st-century learning and to identify the obstacles encountered in applying this approach. The research method used is a literature review that gathers various relevant sources on the research topic. From the results of this literature review, it is concluded that teachers need to develop and update their competencies in pedagogy, professionalism, social skills, and personality to keep up with the latest developments in science and technology. Three components of professional teacher competencies that need to be mastered in the digital technology era of the 21st century are being inspirational and creative-innovative, understanding and skilled in using digital technology, and understanding local and global issues. Keywords: 21st century learning, challenges, elementary schools